Diabetes in the Latino Population in the United States. - O'Brien, Rebecca (My University, 2009)
Latinos in the United States are twice as likely to develop type 2 diabetes as non-Hispanic whites. This study examines possible factors contributing to the prevalence of diabetes in the Latino population: acculturation, lack of access to healthcare, language and cultural barriers, a genetic propensity towards obesity, and organochlorine pesticides.
Color poster with text, images, and graphs describing research conducted by Rebecca O'Brien, advised by Julie A. Anderson.
Keywords: Diabetes--Sociological aspects; Hispanic Americans--Diseases; Hispanic Americans--Health and hygiene; Posters